VIRTUAL SPACE IN THE STRUCTURAL DESIGN OF THE GENRE FIELD OF MODERN DRAMATURGY - Bondareva О. E. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article is devoted to the issue of the day of modern dramaturgy, in particular to the structure of design of its genre field. Creation of virtual space under act of postmodern discourse is created.